Instruction to appoint experienced architect and MEP engineer to supervise the finishing works and MEP works of BRAC University new campus project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding instruction to appoint experienced architect and MEP engineer to supervise the finishing works and MEP works of BRAC University new campus project.